1992
DOI: 10.1136/bmj.305.6855.684
|View full text |Cite
|
Sign up to set email alerts
|

Use of symptoms and signs to diagnose maxillary sinusitis in general practice: comparison with ultrasonography.

Abstract: Objective-To establish the incidence ofmaxillary sinusitis in general practice and the predictive value of symptoms and signs.Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 17 publications
6
34
0
1
Order By: Relevance
“…Sixty-three percent of the patients had radiological signs of sinusitis. This is consistent with the findings of the Dutch study (21) and an investigation of the general practioners' own assessment of the difficulty and clinical uncertainty of this diagnosis (1 1). Of the patients with a clinically diagnosed acute sinusitis 24% had negative CT images, and 13% had moderate mucosal changes.…”
Section: Interobserver Variationsupporting
confidence: 90%
See 2 more Smart Citations
“…Sixty-three percent of the patients had radiological signs of sinusitis. This is consistent with the findings of the Dutch study (21) and an investigation of the general practioners' own assessment of the difficulty and clinical uncertainty of this diagnosis (1 1). Of the patients with a clinically diagnosed acute sinusitis 24% had negative CT images, and 13% had moderate mucosal changes.…”
Section: Interobserver Variationsupporting
confidence: 90%
“…Clinical diagnosis of acute sinusitis is not accurate (7,21). In the Dutch study, clinical diagnosis was confirmed by ultrasonography in less than half of the diagnosed episodes (21).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…With respect to the disagreements in the timing of decision, the uncertainty of the diagnosis might be an important reason (17), and the uncertainty of the effectiveness of antibiotics might also play a role. Waiting while providing patients with information and prescribing analgesics and/or prescribing local therapy (nasal spray) were important management options.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Clinical decision rules have been proposed but have not been prospectively validated. [7][8][9][10][11] Also, many previous studies of individual tests or clinical decision rules have used radiography or computed tomographic (CT) scans as the ref-erence standard, tests that themselves have limited accuracy. 12 Although a CT scan is highly sensitive for the detection of fluid in the sinuses, this fluid may also be caused by a viral infection, so the test lacks specificity and is, therefore, a suboptimal reference standard.…”
Section: Introductionmentioning
confidence: 99%